Managerial Biases and Debt Contract Design: The Case of Syndicated Loans - Adam, Tim R.; Burg, Valentin; Scheinert, Tobias; Streitz, Daniel (Management Science, 2020)
We examine whether managerial overconfidence impacts the use of performance-pricing provisions in loan contracts (performance-sensitive debt [PSD]). Managers with biased views may issue PSD because they consider this form of debt to be mispriced. Our evidence shows that overconfident managers are more likely to issue rate-increasing PSD than regular debt. They choose PSD with steeper performance-pricing schedules than those chosen by rational managers. We reject the possibility that overconfident managers have (persistent) positive private information and use PSD for signaling. Finally, firms seem to benefit less from using PSD ex post if they are managed by overconfident rather than rational managers. This paper was accepted by Gustavo Manso, finance.